El cristiano errante: entre la encrucijada discursiva y el desencanto utópico - Chen Sham, Jorge (2004)
As proposed by the Rationalists. political economy and moral philosopy go hand in hand in El cristiano errante and solely through an examination of it can one begin to comprehend its historical reprecussions. The ambiguity of the critique of the study, and its generic references, drive us to a fundamental problem that can only be resolved when we take into consideration that the narrative at the end of the 18th century and the beginning of the 19th the field generates discursive forms and genres that have as a common denominator the notion that literature can be a critique of society and map out a new American reality.